Peculiarities of Mineral Nutrition of Cereals in Aluminum-Acid Soil Conditions (Chemical and Structure Modification of Polymers, 2015)
Abstract ... 77 7.1 Introduction ... 78 7.2 Materials and Methodology ... 83 7.3 Results and Discussion ... 85 7.4 Conclusion ... 95 Keywords ... 96 References ... 96ABSTRACTInfluence of aluminum ions on requirements of plants of cereal crops (wheat Triticum aestivum L. and oats Avena sativa L.) in macronutrients isstudied. In the first series of experiments it is revealed that doubling of a dose of phosphorus in the acid media has caused doubling of its inclusion in metabolic processes in aluminum-resistant wheat Irgina on early stages of development already, but in aluminum-sensitive wheat Priokskaya – only on a flowering stage. Development of root systems in wheat varieties differ in their Al-resistance level in the conditions of full supply with nitrogen and potassium does not depends on presence of ions of hydrogen, aluminum or phosphorus in soil. Aluminum-sensitive wheat variety is characterized by considerable dependence of photosynthesis on conditions of a mineral nutrition whereas intensity of photosynthetic processes of aluminum-resistant variety is influenced basically by a development stage.